Efficient charge transfer at a homogeneously distributed (NH4)2Mo3S13/WSe2 heterojunction for solar hydrogen evolution. Issue 17 (11th April 2019) - Bozheyev, Farabi; Xi, Fanxing; Plate, Paul; Dittrich, Thomas; Fiechter, Sebastian; Ellmer, Klaus
Abstract : Efficient charge transfer is achieved by coating WSe2 photocathodes with an earth abundant photocatalyst – ammonium thiomolybdate (NH4 )2 Mo3 S13 . Abstract : Highly (00.1)-textured polycrystalline WSe2 films are developed as hydrogen evolving photoelectrodes and improved through deposition of a thin ammonium thiomolybdate (NH4 )2 Mo3 S13 catalyst film. This semiconducting thiomolybdate forms a heterojunction with the p-type WSe2 film passivating recombination centers of excited electron–hole pairs at the edges of the (00.1) textured WSe2 nanoflakes. In addition, thiomolybdate acts as a photoelectrocatalyst at the electrode – aqueous electrolyte interface during light-driven hydrogen evolution. Whereas the photoelectrochemical activity of pure WSe2 is dominated by charge carrier recombination processes at edge states of the hexagonal nanoflakes, we obtain homogeneous charge transfer across the van der Waals planes concomitant with the passivation of these edge states. A photocurrent density of up to 5.6 mA cm −2 at 0 V vs. RHE is obtained with the proposed homogeneously distributed (NH4 )2 Mo3 S13 /WSe2 heterojunction system under AM 1.5 illumination in the 0.5 M H2 SO4 electrolyte. We conclude that homogeneously distributed semiconducting catalysts on the van der Waals planes of WSe2 nano-crystallites are a feasible strategy towards solar hydrogen evolution with large-area photoelectrocathodes.